Mineralogical, Microstructural and Compressive Strength Characterization of Fly Ash as Materials in Geopolymer Cement - Cut Rahmawati; Sri Aprilia; Taufiq Saidi; Teuku Budi Aulia (Elkawnie, 2021)
Abstract: This study was designed to examine the mineral, microstructural, and mechanical strength properties of fly ash and its feasibility as a raw material for geopolymer cement. The study used an experimental method by examining the characteristics of fly ash by X-ray Fluorescence Spectrometer (XRF), Fourier transform infrared (FTIR) spectroscopy, X-ray diffraction (XRD), hydrometer method, Scanning electron microscopy (SEM), and compressive strength testing. For creating the geopolymer cement paste, a concentration of NaOH 10M was used, with a ratio of water/solid = 0.4 and a ratio of Na2SiO3/NaOH = 1 using curring at room temperature. The results showed the geopolymer pastes have a compressive strength of 18.1 MPa and 21.5 MPa after 7 days and 28 days. The XRD results showed a decrease in the peak of 2θ at 26.54° because the amorphous part had transformed into a C-S-H solution in geopolymer cement. This finding was supported by the FTIR spectra results showing Si-O-Si bending vibration and the functional group of AlO2. It showed that Nagan Raya fly ash-based geopolymer is a potential construction material.Abstrak: Penelitian ini dirancang untuk mendapatkan sifat mineral, mikrostruktural, dan kekuatan mekanis dari fly ash serta kesesuaiannya sebagai material dasar pada semen geopolimer. Metode penelitian yang digunakan adalah metode eksperimen dengan cara  menguji karakteristik dari fly ash dengan pengujian X-ray Fluorescense Spectrometer (XRF), Fourier transform infrared (FTIR) spectoscopy, X-ray diffraction (XRD), hydrometer method, Scanning electron microscopy (SEM) dan kuat tekan.  Untuk pembuatan pasta semen geopolimer digunakan konsentrasi NaOH 10 M, rasio water/solid 0,4 dan rasio Na2SiO3/NaOH = 1 dengan perawatan pada suhu kamar. Hasil menunjukkan setelah 7 hari pasta geopolimer memiliki kuat tekan 18,1 MPa dan 21,5 MPa pada 28 hari. Hasil XRD menunjukkan adanya penurunan puncak 2θ pada 26,54° ini disebabkan karena bagian amorf dari fly ash telah menjadi larutan C-S-H pada semen geopolimer. Hasil ini diperkuat dengan analisis FTIR spectra yang menunjukkan adanya Si-O-Si bending vibration dan gugus fungsi dari AlO2. Hasil menunjukkan fly ash dari Nagan Raya potensial sebagai bahan material konstruksi berbasis geopolimer.